Gene expression profiling reveals molecular marker candidates of laryngeal squamous cell carcinoma - Colombo, Jucimara [UNESP]; Fachel, Angela A.; Calmon, Marilia de Freitas [UNESP]; Cury, Patricia Maluf; Fukuyama, Erica Erina; Tajara, Eloiza Helena; Cordeiro, Jose Antonio; Verjovski-Almeida, Sergio; Reis, Eduardo M.; Rahal, Paula [UNESP] (Spandidos Publ Ltd, 2009)
Laryngeal squamous cell carcinoma is very common in head and neck cancer, with high mortality rates and poor prognosis. In this study, we compared expression profiles of clinical samples from 13 larynx tumors and 10 non-neoplastic larynx tissues using a custom-built cDNA microarray containing 331 probes for 284 genes previously identified by informatics analysis of EST databases as markers of head and neck tumors. Thirty-five genes showed statistically significant differences (SNR >= 11.01, p <= 0.001) in the expression between tumor and non-tumor larynx tissue samples. Functional annotation indicated that these genes are involved in cellular processes relevant to the cancer phenotype, such as apoptosis, cell cycle, DNA repair, proteolysis, protease inhibition, signal transduction and transcriptional regulation. Six of the identified transcripts map to intronic regions of protein-coding genes and may comprise non-annotated exons or as yet uncharacterized long ncRNAs with a regulatory role in the gene expression program of larynx tissue. The differential expression of 10 of these genes (ADCY6, AES, AL2SCR3, CRR9, CSTB, DUSP1, MAP3K5, PLAT, UBL1 and ZNF706) was independently confirmed by quantitative real-time RT-PCR. Among these, the CSTB gene product has cysteine protease inhibitor activity that has been associated with an antimetastatic function. Interestingly, CSTB showed a low expression in the tumor samples analyzed (p<0.0001). The set of genes identified here contribute to a better understanding of the molecular basis of larynx cancer, and provide candidate markers for improving diagnosis, prognosis and treatment of this carcinoma.
Keywords: cDNA microarray; Larynx carcinoma; Gene expression; Real time RT-PCR; cystatin B